The Ammonium Excreting Azospirillum brasilense Strain HM053 Enhances the Vegetative Development of Strawberry - Helyemari Valentim Althaus; Camila Audrey dos Reis; Carolina Weigert Galvão; Rafael Mazer Etto; Ricardo Antonio Ayub (Brazilian Archives of Biology and Technology, 2025)
Abstract Strawberry is a small fruit with high commercial value and is globally appreciated for its organoleptic and nutraceutical characteristics. However, its production necessitates substantial inputs of nitrogen fertilizers, resulting in elevated production costs and environmental harm. Plant growth-promoting bacteria have been gaining prominence in sustainable agriculture for their ability to stimulate plant growth and partially replace nitrogen fertilizers. Among these microorganisms, the genus Azospirillum stands out as one of the most promising; nevertheless, its utilization in growing small fruits has received less attention. This study aimed to evaluate the impact of Azospirillum biofertilization on greenhouse-grown strawberry crops. For this, two strains from this genus (A. brasilense Ab-V5 and HM053), were individually evaluated in association with four different nitrogen doses. Additionally, two different inoculation methods were employed: soil inoculation and leaf aspersion. The research was conducted using a completely randomized design, with one strawberry plant per pot and six repetitions per treatment. The results indicate that the Florida Festival strawberry crop responded positively to inoculation with A. brasilense HM053 and Ab-V5. The best results were observed for plants inoculated with HM053 associated with 50% nitrogen, which achieved results comparable to treatments with a full dose of nitrogen and without inoculation and also showed a 2.74% increase in shoot fresh weight compared to the control. This could indicate a 50% reduction in the use of nitrogen fertilizer; reducing production costs by approximately 32 dollars per cultivated hectare, making A. brasilense HM053 a promising biofertilizer for strawberry cultivation.